Response to intervention: changing the way we teach our children - Schmitz, Tara Jean (My University, 2010)
Passed on January 2, 2002, the No Child Left Behind Act has changed the way educators are looking at their student population. No longer are students in the wait- to- fail routine nor are they referred to Special Education for all minor or major discrepancies between their abilities and those of their peers. The nation today is implementing a multi-tiered, data-driven decision making procedure known as Response to Intervention to replace the learning disability discrepancy model which has been used for many years. Response to Intervention is a time consuming method used to intervene early to possibly detract from one's need for special education service. This thesis examines the good, the bad, and the ugly of Response to Intervention.
Keywords: Learning disabled children -- services for.; Effective teaching.; Learning disabilities.; Child development.; Individual differences in children.; Cognition in children.; Learning.